DEMONSTRATION OF THE PRIMING EFFECT THROUGH BEHAVIORAL BEHAVIORS IN AN INTERMEDIATE CITY - Vera Reino, José; Guevara Crespo, Nicole (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Ignorance of the behavior derived from exposure to food advertising is a topic of interest for society, academia and state as well as for the business area, more deeply in a teenage public. The present investigation starts from the hypothesis, that the nutritional behavior of the individuals, can be automatic and unconscious, during the visualization of a program with food advertising content. This experiment is carried out with adolescents from 12 to 18 years of age, in an intermediate citizen in South America; divided into two groups, the first, which is subjected to the observation of food advertising and a control group exempt from it, during the presentation of a cirsences skills program. Food consumption will be evaluated throughout the audiovisual exhibition, through the qualitative analysis of behavioral behaviors. An increase in food intake was evidenced in the group that was subjected to food advertising exposure, and differences were observed in the composition by age ranges, demonstrating the existence of the priming effect in adolescents.